ASEAN Charter and Regional Micro, Small and Medium Enterprises Development - Daties, Dyah Ridhul Airin; Peilouw, Johanis Steny Franco (Balobe Law Journal, 2023)
Introduction: Micro, Small and Medium Enterprises (MSMEs) are a prominent sector in the Asian region that is proven to support the economy, especially developing countries. Although important, it is not uncommon for countries to ignore these independent economic initiatives.Purposes of the Research: This paper aims to provide a brief overview of ASEAN's role in the development of MSMEs in the Region which is the mandate of the ASEAN Charter.Methods of the Research: This research was conducted by conducting a normative juridical approach. Literature review and related secondary data.Results of the Research: The results showed that MSMEs are one of the efforts to realize the economic goals of the Region as stated in the ASEAN Charter. Behind its strategic role for the national and regional economies, MSMEs still often face various challenges, both internally, such as limited capital and technology, as well as externally, including issues related to licensing, raw materials, marketing to integration efforts into regional and global production chains. For this reason, ASEAN's role is very important, especially to implement the Strategic Action Plan for SME Development (SAPSMED) 2016-2025 with the vision of 'Globally Competitive and Innovative SME’.